(untitled) (International Research Journal of Management and Social Sciences, 2024)
Purpose: The study aims to examine the dual effects of task significance on innovative work behavior through cognitive appraisal and work engagement, while considering PsyCap's moderating function. Design/methodology/approach: Current study is quantitative and for this structured questionnaire was used to collect primary data from nurses employed at tertiary hospitals of twin cities of Pakistan. Findings: The results of the study support the idea that task significance is a special kind of stressor that can have both positive and negative effects. Employee engagement and innovative work behavior are boosted by challenge appraisal of task significance, whereas they are hindered by threat appraisal. Therefore, nursing management must create measures (such as training for developing PsyCap) to impact nurses' perceptions of task significance as challenges rather than threats to promote nurses' innovative work behavior. Originality: The current study is original and has not been conducted and submitted earlier to any other journal.